Divergent evolution in the polymorphic granular poison‐dart frog, Oophaga granulifera: genetics, coloration, advertisement calls and morphology. (18th October 2012) - Brusa, Oscar; Bellati, Adriana; Meuche, Ivonne; Mundy, Nicholas I.; Pröhl, Heike; Rocha, Luiz
Abstract Aim To investigate the intra‐specific genetic divergence and phenotypic diversification in Oophaga granulifera, analysing phylogeographical patterns, population structure, coloration and traits potentially involved in reproductive isolation. Location Costa Rica. Methods Our phylogeographical analysis used the mitochondrial genes cytochrome b and 16S. We sequenced the two markers in 28 individuals belonging to 10 populations and 16 individuals from nine populations, respectively. The population structure was analysed based on seven polymorphic microsatellite loci in 7–15 individuals from 11 populations using maximum likelihood and Bayesian analyses. The colour phenotypes of 189 frogs and the reflectance spectra of 15 frogs from five populations were measured. In nine populations, we recorded the advertisement calls of 59 males and measured 10 morphological variables from 147 frogs. Results Our phylogeographical reconstruction supported the divergence into southern and northern lineages in O. granulifera. In a colour transition area between the main red and green morphs, we describe novel gradual intermediate phenotypes occurring in polymorphic populations. The colour distribution was asymmetrical compared to the genetic variation: the southern lineage included only monomorphic red populations while the northern lineage contained red, green and polymorphic populations. The two lineages differed significantly in advertisement calls and morphology. Microsatellites confirmed the clear inter‐lineage divergence. In the northern lineage, the red morph differed from the intermediate and green morphs in the pulse rate of the advertisement call and in body size. In the colour transition area, there was no simple genetic or colour cline. Main conclusions Oophaga granulifera has evolved into two genetic lineages. The reduced gene flow and diversification in advertisement calls and morphology point to reproductive isolation between lineages. Within the northern lineage, the presence of gradual intermediate morphs and the population structure support the presence of gene flow across the colour transition area while the red versus intermediate–green divergence in both calls and morphology reveals the potential for assortative mating. Our data all congruently show that O. granulifera presents deep intra‐specific divergence. The lack of genetic diversification among colour morphs and the genetic connectivity among the populations defining the colour transition area suggest that the colour diversification in the species is a recent phenomenon.